Change in the position of the axis of rotation in the body of the Earth: the cause, mechanism and use for explaining global tectonic processes in the earth's crust - K. F. Tyapkin (Геофизический журнал, 2012)
Data on alternating continental and oceanic conditions in the near surface part of the Earth within the geologic stage of its development are noted. The alternation is explained by change of the Earth’s rotation axis. Some reasons and mechanisms of this phenomenon are considered. Possibility to determine the pole locations in the near past is illustrated by the example of the North Atlantic coastal terrace. Finally, we hope that the issues discussed in the paper will promote a more friendly perception of the New rotation hypothesis of the structure formation in the Earth’s tectonosphere.